PREDICTING SHEAR VISCOSITY DURING VOLCANIC PROCESSES AT THE GLASS TRANSITION: A CALORIMETRIC CALIBRATION - Gottsmann J.; Giordano D.; Dingwell D.B. (My University, 2002)
The viscosity of volcanic melts at the glass transition has been determined for 11 compositions ranging from basanite to rhyolite. Determination of the temperature dependence of viscosity, together with the cooling rate dependence of the glass transition, permits the calibration of the value of the viscosity at the glass transition at a given cooling rate for each melt. Temperature-dependent viscosities have been obtained using micropenetration methods in the range 108-1012 Pa s. Glass transition temperatures have been obtained using differential scanning calorimetry. For each investigated melt composition, the activation energies yielded by calorimetry and viscometry are identical. This confirms that a simple shift factor can be used for each in order to determine the viscosity at the glass transition for a given cooling rate in nature. The results of this study indicate that there is a subtle but significant compositional dependence of the shift factor of a factor of 10 (in log terms) from 10.8 to 9.8. The composition dependence of the shift factor is cast here in terms of a compositional parameter, the mol% of excess oxides (defined within). Using such a parameterisation we obtain a non-linear dependence of the shift factor upon composition that matches the 17 observed values within error. The resulting model permits the prediction of viscosity at the glass transition, during the cooling of glassy volcanic rocks to within 0.1 log units.
Keywords: VISCOSITY; ENTHALPY; RELAXATION; MAGMAS; LAVA; VOLCANISM; ERUPTIONS; PHASE TRANSITIONS